2005
DOI: 10.1111/j.1440-1797.2005.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

QT interval dispersion in dialysis patients

Abstract: SUMMARY:The leading cause of mortality in dialysis patients is cardiovascular complications, including ventricular arrhythmias and sudden cardiac death. A reliable non-invasive predictive test of sudden death is therefore important. The interlead variation in duration of the QT interval on the surface electrocardiogram corrected with heart rate (QTc dispersion) might serve as a surrogate for ventricular arrhythmia. Prolonged QTc dispersion is commonly encountered in dialysis patients and possesses an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 40 publications
5
50
1
4
Order By: Relevance
“…Prolongation of QT interval and increased QT dispersion in end stage renal disease are subjects of interest for a long time. Previously published articles mainly point out similar findings: these indices of sudden death on the surface ECG are significantly higher in patients receiving HD [6,14]. Hemodialysis itself is pro-arrhythmogenic, but also there is high variety of comorbidities in end stage renal disease patient population.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Prolongation of QT interval and increased QT dispersion in end stage renal disease are subjects of interest for a long time. Previously published articles mainly point out similar findings: these indices of sudden death on the surface ECG are significantly higher in patients receiving HD [6,14]. Hemodialysis itself is pro-arrhythmogenic, but also there is high variety of comorbidities in end stage renal disease patient population.…”
Section: Discussionmentioning
confidence: 58%
“…These indices mainly depend on the QT interval [6,7]. Prolongation of QT interval, dispersion of QT interval; which is calculated by extracting minimum measured QT interval from maximum measured QT interval, were widely utilized in many studies and were shown to be related with increased sudden death risk in HD patients [8][9][10][11][12][13][14]. Recent studies indicate that prolongation of the T wave peak to T wave end interval (Tp-e) on the 12-lead ECG is a marker of ventricular arrhythmogenesis [15][16].…”
mentioning
confidence: 99%
“…On se izračunava pomoću Bazettove formule: QTc = , gde RR predstavlja dužinu između dve depolarizacije komora u milisekundama. Kod bolesnika na hemodijalizi QTc veći od 500 ms ukazuje na povećan rizik od komorskih poremećaja srčanog ritma (36,37). Standardni EKG pruža mogućnost da se proceni promenljivost trajanja QT intervala (disperzija QTc intervala).…”
Section: Otkrivanje Bolesnika Sa Povećanim Rizikom Od Iznenadne Srčanunclassified
“…Promenljivost korigovanog QTc intervala koristi se za procenu rizika od nastanka komorskih poremećaja srčanog ritma kod bolesnika na hemodijalizi. Promenljivost QTc intervala definiše se kao razlika između najdužeg i najkraćeg QTc intervala registrovanog standardnim elektrokardiogramom (36,37). Normalna promenljivost QTc intervala iznosi 40-50 ms. Kod bolesnika na hemodijalizi, kod kojih je promenljivost QTc intervala veća od 50 ms postoji povećan rizik od nastanka komorskih poremećaja srčanog ritma i iznenadne srčane smrti (36,37).…”
Section: Otkrivanje Bolesnika Sa Povećanim Rizikom Od Iznenadne Srčanunclassified
“…These indices mainly depend on the QT interval [10,11] Prolongation of QT interval, dispersion of QT interval; which is calculated by extracting minimum measured QT interval from maximum measured QT interval, were widely utilized in many studies and were shown to be related with increased sudden death risk in HD patients [12][13][14].…”
Section: Introductionmentioning
confidence: 99%